The CREB‐binding protein affects the circadian regulation of behaviour. Issue 18 (28th August 2016) - Maurer, Christian; Winter, Tobias; Chen, Siwei; Hung, Hsiu‐Cheng; Weber, Frank
Abstract : Rhythmic changes in light and temperature conditions form the primary environmental cues that synchronize the molecular circadian clock of most species with the external cycles of day and night. Previous studies established a role for the CREB‐binding protein (CBP) in molecular clock function by coactivation of circadian transcription. Here, we report that moderately increased levels of CBP strongly dampen circadian behavioural rhythms without affecting molecular oscillations of circadian transcription. Interestingly, light–dark cycles as well as high temperature facilitated a circadian control of behavioural activity. Based on these observations we propose that in addition to its coactivator function for circadian transcription, CBP is involved in the regulation of circadian behaviour down‐stream of the circadian clock. Abstract :